Customer Satisfaction Analysis At Zun Motor East Lombok Workshop - Adam Semedhi Permana; Muh.Fahrurrozi; Isfi Sholihah (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
This study aims to determine the effect of Service Quality, Price Perception and Facilities on Consumer Satisfaction in Zun Motor East Lombok workshop. This research is a type of associative research using primary data collected through questionnaires and interviews. Then the data were processed using descriptive statistical analysis techniques, classical assumption tests, multiple linear regression, and hypothesis tests (t table and f table) with the help of SPSS 22. The population of this study was all customers who visited the Zun Motor East Lombok workshop, with only 50 people taking as research samples. The results of this research hypothesis test show that there is a positive and significant influence given by Service Quality, Price Perception and Facilities on Consumer Satisfaction. Next, in the coefficient of determination test, data results of 21.1% were obtained which can be explained by digital literacy and entrepreneur behavior. While the remaining 78.9% can be explained by the influence of other variables not studied by the authors.